Developmental Disability: Families and Functioning in Child and Adolescence - Rosenbaum, Peter (Frontiers in Rehabilitation Sciences, 2021)
The WHO’s ICF framework for health provides an integrated approach to health for everyone. Several aspects of this framework allow us to see people’s lives in a richer and more holistic manner than has traditionally been the case based on diagnosis alone. These features include the positive language (emphasizing in particular ‘activity’, ‘participation’, and ‘personal factors’); the interconnections of the parts of this ‘dynamic system’, in which every component can influence every other one; and the formal inclusion of ‘contextual factors’ – personal and environmental – that are otherwise too easy to take for granted and then ignore. This paper addresses the ‘environmental’ dimension of the ICF framework – specifically referring to ‘family’ as the central environmental force in the lives of children and adolescents. The perspectives of the author are those of a ‘developmental paediatrician’, whose career has focused on children with conditions that challenge their development, and their families. Lessons learned from a lifetime of this work – including teaching and research as well as clinical services – are offered. Particular emphases will be on (i) the importance of focusing on the family in a nonjudgmental ‘family-centred’ way; (ii) how conceptual ideas about child (and family) development and parenting are as important as technical approaches to intervention; and (iii) how the ICF framework ‘allows’ – indeed encourages – such a focus to have value and importance equal to the best of biomedical interventions. Examples from current research will illustrate how these ideas can be implemented.